Hubungan Karakteristik, Pengetahuan dengan Stigma Petugas Kesehatan Tentang Koinfeksi Tuberkulosis-Virus Human Immunodeficiency di Kota Manado - Salmon, Deni; Kandou, Grace D.; Palandeng, Henry M.F.; Porajow, Zwingly C.J.G.; Pakasi, Trevino A. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Tuberculosis and human immunodeficiency virus (HIV) are two issues of public health which has become concern inthe world. HIV related stigma is a major barrier to treatment. Many cases of AIDS have been found compered hiv positiveraised the question how is hiv services in manado city. This study aims to determine the correlation betweencharacteristic, knowledge with stigma of health care workers about tuberculosis-human immunodeficiency virus coinfectionsin Manado city. The method of this research is analytical with cross-sectional design was conducted at fiveclinic of Manado city. Ninety seven health care workers were included in this study and they were selected proportion.Bivariat analysis (chi-square) was used to identify the correlations between characteristic, knowledge with stigmatizedattitudes. The result of research indicates that the level of stigmatized attitudes was high. Chi-square testshowed a correlation (p<0,05) between characteristic based on age with stigmatized attitudes, characteristic based onjob with stigmatized attitudes, characteristic based on years of experience with stigmatized attitudes, and knowledgewith stigmatized attitudes. Conclusion: There are a correlation between characteristic based on age, job, years of experienceand knowledge with stigmatized attitudes.Keywords: Characteristic, knowledge, stigma, health care workers, TB-HIV co-infection.